Improving ultra-fast charging performance and durability of all solid state thin film Li-NMC battery-on-chip systems by in situ TEM lamella analysis. (March 2022) - Romano Brandt, León; Nishio, Kazunori; Salvati, Enrico; Simon, Kevin P.; Papadaki, Chrysanthi; Hitosugi, Taro; Korsunsky, Alexander M.
Highlights: Novel all solid state NMC-based micro-battery system studied using in-situ SEM charging. Record charging rate achieved with full preservation of integrity of the cathode-solid electrolyte interface. Residual stress analysis in charge cycled samples reveals the origins of mechanical damage and sets targets for achieving improved performance. Abstract: All solid state, thin film Li-NMC batteries produced by Physical Vapour Deposition have the potential to revolutionize the internet of things by integrating ultra-fast charging and high energy densities into small portable devices. In these systems, the integrity of the cathode-solid electrolyte interface is of particular importance, as it determines the internal battery resistance and attainable charge rate. To understand and control the effect of manufacturing parameters on the performance and interface stability in these systems, as well as the mechanisms resulting in interface degradation, a novel approach was used that combined in situ battery lamella charging with electron nano-diffraction and multiphysics Finite Element modeling. Experimentally observed cathode strains and degradation were correlated with deposition parameter-controlled grain orientation, to determine ideal deposition conditions for enhanced thin film battery charging and discharging behavior. It was identified that (104) oriented cathode grains minimize anode-electrolyte interface degradation, while allowing for high charge and discharge rates, as well as significantly reducing the cathode-electrolyte interface resistance. Furthermore, the residual stress state of individual thin film battery layers, as well as the cathode grain orientation were identified as material design parameters to optimize cell performance and durability with potential capacity retention enhancements of up to 28%. Graphical abstract: Image, graphical abstract